2013
DOI: 10.1590/0074-0276130207
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib activity on Schistosoma mansoni

Abstract: Imatinib, a drug used for treatment of human chronic myeloid leukaemia, due to its activity against protein kinases, has been also evaluated in vitro against Schistosoma mansoni showing high schistosomicidal activity. In the present experiments imatinib activity in vitro was confirmed at the doses of 25 µM, 50 µM and 100 µM. The first drug activity observed with the lower dose was interruption of egg-laying and with the higher dosages was the death of the worms. In mice infected with S. mansoni no activity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…This was confirmed by an independent approach recently, which reproduced similar phenotypes in vitro , although a first in vivo experiment failed [106]. Nonetheless, the data obtained in this study support the conclusion that Imatinib exerts broad negative effects on worm physiology substantiating the hypothesized role of PKs as potential targets [25], [28], [36], [42], [43].…”
Section: Discussionsupporting
confidence: 86%
“…This was confirmed by an independent approach recently, which reproduced similar phenotypes in vitro , although a first in vivo experiment failed [106]. Nonetheless, the data obtained in this study support the conclusion that Imatinib exerts broad negative effects on worm physiology substantiating the hypothesized role of PKs as potential targets [25], [28], [36], [42], [43].…”
Section: Discussionsupporting
confidence: 86%
“…Experiments involving animal (rodent) models of infection are then required to confirm the effects observed in vitro . However, very often in vivo studies fail in this regard ( Keiser, 2010; Rodriguez et al, 2010; Murthy et al, 2011; Da’dara et al, 2013; Katz et al, 2013; Soeiro et al, 2013 ; this study). Likewise, our studies with Imatinib suggest that there is a remarkable discrepancy between the in vivo and the vitro results that registered dramatic effects on adults ( Beckmann and Grevelding, 2010; Beckmann et al, 2012 ) and schistosomula (this study), and the lack of schistosomicidal activity in vivo ( Katz et al, 2013 ; this study).…”
Section: Discussionmentioning
confidence: 95%
“…However, very often in vivo studies fail in this regard ( Keiser, 2010; Rodriguez et al, 2010; Murthy et al, 2011; Da’dara et al, 2013; Katz et al, 2013; Soeiro et al, 2013 ; this study). Likewise, our studies with Imatinib suggest that there is a remarkable discrepancy between the in vivo and the vitro results that registered dramatic effects on adults ( Beckmann and Grevelding, 2010; Beckmann et al, 2012 ) and schistosomula (this study), and the lack of schistosomicidal activity in vivo ( Katz et al, 2013 ; this study). This unexpected result corresponded to (i) similar treatment experiments with schistosome-infected hamsters, in which compared to the mouse model even higher plasma concentrations of Imatinib were determined (about 42 μM after 30 min and about 12 μM after 6 h following a 60 mg/kg dosage; data not shown) but also (ii) to recent data obtained in a parallel study where Imatinib treatment of adult worms showed similar in vitro effects but no obvious in vivo effects in mice treated with up to even 1000 mg/kg ( Katz et al, 2013 ).…”
Section: Discussionmentioning
confidence: 95%
“…The one exception was imatinib (Gleevec), a successful anti-leukemia agent, which was shown to be lethal to adult worms in vitro at high concentrations ( Beckman and Grevelding, 2010 ). However, imatinib was ineffective in an S. mansoni infection model ( Table 1 ) ( Katz et al, 2013 ) which is not surprising, as the drug is highly bound to alpha-1-acid glycoprotein ( Soo et al 2010 ).…”
Section: Schistosomiasis and Food-borne Trematodiasesmentioning
confidence: 99%